The influence of transformational leadership on ASN performance through the core values of ethical ASN at the BKPSDM Tebing Tinggi City - Zufira Feby Ivanka; Hazmanan Khair (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of transformational leadership on the performance of State Civil Apparatus (ASN) through the Core Values ??of ASN BerAKHLAK at the BKPSDM of Tebing Tinggi City. This study uses a quantitative approach with data collection techniques through distributing questionnaires to 42 ASN respondents at the BKPSDM of Tebing Tinggi City. Data analysis methods used include validity tests, reliability tests, classical assumption tests, and mediation analysis using the Jamovi application through the Mediation Analysis feature in the medmod module. The validity test was carried out using Pearson Product Moment, while the reliability test used Cronbach's Alpha. The results of the study indicate that transformational leadership has a positive effect on the Core Values ??of ASN BerAKHLAK. Furthermore, the Core Values ??of ASN BerAKHLAK have a positive and significant effect on ASN performance. Transformational leadership also has a positive effect on ASN performance. In addition, the results of the mediation analysis show that the Core Values ??of ASN BerAKHLAK are able to mediate the effect of transformational leadership on ASN performance at the BKPSDM of Tebing Tinggi City.